Structuring water transport pathway of chitosan/poly(vinyl alcohol) hydrogels towards achieving high-efficiency and salt-resistive solar desalination - Yuankun Wang; Feng Wang; Yu Lu; Defeng Wu (Carbohydrate Polymers, 2026)

Solar-driven dye wastewater purification and synergistic desalination by an aerogel-based multitasking platform structured with polydopamine-hybridized covalent organic frameworks - Feng Wang; Zequan Shen; Hui Wang; Yuheng Zhang; Baoxia Dong; Defeng Wu (Journal of Hazardous Materials, 2026)

Reutilization of digestate (residue and liquid) in the anaerobic digestion of sole corn stover: biochar preparation, methane performance and microbial responses - Haipeng Wang; Hao Sun; Sheng-Nan Zhuo; Jianrui Li; Zetang Chai; Jingwen Jia; Guangli Cao; Guo-Jun Xie; Defeng Xing; Nan-Qi Ren; Bing-Feng Liu (Journal of Environmental Management, 2026)

Development of a Sensitive Real‐Time PCR Method for Detection of Carp Oedema Virus - Huilin He; Ruixue Feng; Siyi Guo; Bing Han; Jinshan Huang; Xu Lin; Jiyuan Yin; Defeng Zhang; Min Liu; Wen Shi (Journal of Fish Diseases, 2026)
Carp oedema virus disease (CEVD), caused by the carp oedema virus (CEV), results in significant economic losses to the common carp and koi aquaculture industry. The CEVD symptoms resemble those of koi herpesvirus (KHV) and include lethargy, swollen gills, sunken eyes, and skin haemorrhages. Consequently, the development of efficient detection methods is imperative for the prevention and diagnosis of CEVD. In this study, we developed a quantitative real‐time PCR assay for the sensitive detection of CEV infection. Specific primers were designed based on a highly conserved region within the CEV p4a gene. The assay exhibited a sensitivity that was 100‐fold greater than that of the conventional PCR technique, with high specificity, and no observed cross‐reactivity with infectious haematopoietic necrosis virus (IHNV), infectious pancreatic necrosis virus (IPNV), spring viremia of carp virus (SVCV), salmonid alphavirus (SAV), or KHV. Inter‐ and intra‐assay experiments also confirmed the method's high repeatability. In a clinical setting, it showed higher sensitivity compared to the diagnostic methods for CEVD developed by the Center for Environment, Fisheries and Aquaculture Science (CEFAS), while also significantly reducing detection costs. Consequently, the established assay could provide robust technical support for the clinical diagnosis and epidemiological investigation of CEVD.

Event-triggered prescribed performance control for trajectory tracking of unmanned surface vehicle under DoS attacks - Siqin Wang; Defeng Wu; Zheng You; Na Feng; Ming Mao (Ocean Engineering, 2026)

Synergistic conversion of CH4 and CO2 into bioplastic by microalgal−bacterial consortia - Xiaowei Lv; Huihui Zhou; Yanlei Niu; Kun Feng; Nanqi Ren; Defeng Xing (Chemical Engineering Journal, 2026)

Concentration-dependent and thermal pretreatment effects of allicin on hydrogen and ethanol co-production from food waste - Jiayin Hao; Huihui Zhou; Kun Feng; Xiaoxue Mei; Nanqi Ren; Defeng Xing (Chemical Engineering Journal, 2026)

Rare Bacterial Taxa Drive Soil Multifunctionality in Lakeside Wetlands of Eutrophic Lake - Lingchen Yuan; Jiajia Zhang; Mengxi Gao; Renlei Yang; Yue Chen; Bin Hu; Defeng Feng; Wei Li (Wetlands, 2026)

Enhancing E. coli removal in mesophilic anaerobic digestion: New insights from inoculum comparison and metagenomic analysis - Haipeng Wang; Zetang Chai; Jianrui Li; Hao Sun; Hong-Yu Ren; Guangli Cao; Guo-Jun Xie; Defeng Xing; Nan-Qi Ren; Bing-Feng Liu (Bioresource Technology, 2025)

Self-regulating adaptability of biofilm microbiomes enhances manganese and ammonia removal in microbial electrochemical filters under dioxane exposure - Sitong Liu; Kun Feng; Dawei Zhang; Yang Liu; Jing Wang; Baiyun Lu; Defeng Xing (Journal of Hazardous Materials, 2025)

Simultaneous denitrification and phosphorus removal in MBfR with methane as the sole carbon source - Xiaowei Lv; Huihui Zhou; Jie Yang; Jiayin Hao; Zheng Zhong; Kun Feng; Defeng Xing (Journal of Environmental Management, 2025)

Reassessing systemic blind spots in modern water disinfection paradigms - Yang Liu; Jialiang Gu; Kun Feng; Yangyang Zhang; Zheng Zhong; Sitong Liu; Defeng Xing (Journal of Hazardous Materials, 2025)

Synthetic microbiome and biochar enhanced human feces aerobic mesophilic composting - Xiaoyu Cai; Jing Wang; Kun Feng; Huihui Zhou; Chuan Chen; Chuandong Wu; Rui Fang; Defeng Xing (Resources, Conservation and Recycling, 2025)

Event-triggered distributed disturbance rejection model predictive control for unmanned surface vehicles under lumped disturbances and input saturation - Na Feng; Defeng Wu; Hongliang Yu; Zheng You (Ocean Engineering, 2025)

Enhanced photocatalytic defluorination of perfluorooctanoic acid through integrated hydrogen atoms/electrons reduction and ROS oxidation with metal–organic framework heterogeneous catalysts - Cai Yan; Zheng Zhong; Jing Wang; Kun Feng; Defeng Xing (Chemical Engineering Journal, 2025)

Applying machine learning and genetic algorithms accelerated for optimizing ethanol production - Xu Yang; Nianhua Chen; Hui Yu; Xinyue Liu; Yujie Feng; Defeng Xing; Yushi Tian (Science of The Total Environment, 2024)

Process exploration of domestication, start-up and rapid recovery strategies for anaerobic digestion of sole corn stover: Methane production efficiency and dominant microbial responses - Haipeng Wang; Hao Sun; Hong-Yu Ren; Guangli Cao; Guo-Jun Xie; Defeng Xing; Nan-Qi Ren; Bing-Feng Liu (Journal of Cleaner Production, 2024)

Improved electrocatalytic activity and CO2 tolerance of iron-based perovskite as an intermediate temperature SOFC cathode - Yunlong Chen; Jiahui Zhu; Tifeng Xia; Yuqing Feng; Jiayi Chang; Xiaofei Zhu; Jinghe Bai; Jianqiu Wang; Wenfu Yan; Defeng Zhou (Fuel, 2024)

Intensified partial nitrification and microbiome response in a membrane pulsing-aerated biofilm reactor - Zheng Zhong; Kun Feng; Yu Chen; Baiyun Lu; Jing Wang; Chuandong Wu; Defeng Xing (Chemical Engineering Journal, 2024)

Efficient removal of hexavalent chromium from wastewater using a novel sodium alginate-biochar composite adsorbent - Yushi Tian; Xiaolin Sun; Nianhua Chen; Xintong Cui; Hui Yu; Yujie Feng; Defeng Xing; Weihua He (Journal of Water Process Engineering, 2024)

Termite mounds affect soil aggregate stability and aggregate-associated phosphorus forms in a tropical rubber plantation - Fangmei Lin; Yanqiang Jin; Chenggang Liu; Yan Ren; Chuan Jiang; Defeng Feng; Jianwei Tang (Plant and Soil, 2024)

Sequential recovery of protein and ammonium from waste sludge and functional metabolism in a combined process of nutrient recovery electro-fermentation (NREF) - Jiayu Gu; Huihui Zhou; Jing Wang; Kun Feng; Guojun Xie; Bingfeng Liu; Defeng Xing (Resources, Conservation and Recycling, 2024)

Land use change alters carbon and nitrogen dynamics mediated by fungal functional guilds within soil aggregates - Chenggang Liu; Yanqiang Jin; Fangmei Lin; Chuan Jiang; Xiaoling Zeng; Defeng Feng; Fuzhao Huang; Jianwei Tang (Science of The Total Environment, 2023)

Understory vegetation management regulates soil carbon and nitrogen storage in rubber plantations - Yan Ren; Fangmei Lin; Chuan Jiang; Jianwei Tang; Zhaofei Fan; Defeng Feng; Xiaoling Zeng; Yanqiang Jin; Chenggang Liu; Olusanya Abiodun Olatunji (Nutrient Cycling in Agroecosystems, 2023)

Mechanisms of magnetic sensing and regulating extracellular electron transfer of electroactive bacteria under magnetic fields - Huihui Zhou; Xianwen Xuanyuan; Xiaowei Lv; Jing Wang; Kun Feng; Chuan Chen; Jun Ma; Defeng Xing (Science of The Total Environment, 2023)

Effects of long-term warming on soil prokaryotic communities in shrub and alpine meadows on the eastern edge of the Qinghai-Tibetan Plateau - Wei Li; Lingchen Yuan; Xianli Lan; Rui Shi; Dongdong Chen; Defeng Feng; Xinquan Zhao; Huai Chen (Applied Soil Ecology, 2023)

Co-treatment with free nitrous acid and calcium peroxide regulates microbiome and metabolic functions of acidogenesis and methanogenesis in sludge anaerobic digestion - Jing Wang; Yu Lou; Dongmei Ma; Kun Feng; Chuan Chen; Lei Zhao; Defeng Xing (Science of The Total Environment, 2023)

Conductive carrier promotes synchronous biofilm formation and granulation of anammox bacteria - Kun Feng; Yu Lou; Yitian Li; Baiyun Lu; Anran Fang; Guojun Xie; Chuan Chen; Defeng Xing (Journal of Hazardous Materials, 2023)

Biochar prepared from human feces (HFBC) as a promoter in biohydrogen production using simulated feces as substrate - Pian-Pian Xu; Kai Sun; Jian Du; Guojun Xie; Defeng Xing; Bing-Feng Liu (Chemical Engineering Journal, 2023)

Variations in bacterial and archaeal community structure and diversity along the soil profiles of a peatland in Southwest China - Wei Li; Mingmo Luo; Rui Shi; Defeng Feng; Zhenan Yang; Huai Chen; Bin Hu (Environmental Science and Pollution Research, 2022)

Comparison of Anaerobic Methane Oxidation in Different Sediment Habitats of Dianchi Lake - Wei Li; Yue Chen; Mingmo Luo; Chunyan Li; Yonggui Zhao; Huai Chen; Defeng Feng; Bin Hu (Water, Air, & Soil Pollution, 2020)

Soil water content and pH drive archaeal distribution patterns in sediment and soils of water-level-fluctuating zones in the East Dongting Lake wetland, China - Wei Li; Defeng Feng; Gang Yang; Zhengmiao Deng; Junpeng Rui; Huai Chen (Environmental Science and Pollution Research, 2019)

Ecosystem carbon stock across a chronosequence of spruce plantations established on cutovers of a high-elevation region - Xueyong Pang; Junsheng Huang; Qingxia Zhao; Defeng Feng; Weikai Bao; Guanglong Tian (Journal of Soils and Sediments, 2017)

Consistent profile pattern and spatial variation of soil C/N/P stoichiometric ratios in the subalpine forests - Defeng Feng; Weikai Bao; Xueyong Pang (Journal of Soils and Sediments, 2017)

Dietary salt modulates the sodium chloride cotransporter expression likely through an aldosterone-mediated WNK4-ERK1/2 signaling pathway - Lingyun Lai; Xiuyan Feng; Defeng Liu; Jing Chen; Yiqian Zhang; Bowen Niu; Yong Gu; Hui Cai (Pflügers Archiv - European Journal of Physiology, 2012)